The role of the humic substances in the fractioning of heavy metals in Rodrigo de Freitas Lagoon, Rio de Janeiro - Brazil. - FONSECA, E. M. da (2014)
One of the main results of the processes related to urbanization is the contamination of the adjacent water bodies. Inserted in this context, the Rodrigo de Freitas lagoon is situated in the south zone of the city of Rio de Janeiro. This ecosystem receives several inputs containing all sorts of pollutants, including heavy metals. The present work aimed to study the partitioning of heavy metals in the sediments of Rodrigo de Freitas and the influence of organic matter in this fractionation dynamic. The results of these analyses presented the contents of organic matter as an important metal-capturing agent. Fractionation of organic matter resulted in a predominance of humine. Heavy metal partitioning showed that the metals bound by the water-soluble phase have no significant concentrations. Special features such as, reducing sediment, high levels of organic matter and fine grain size have transformed this ecosystem in an effective deposit of pollutants, where heavy metals are not available in easily reactive fractions.